Editorial: A tendência da publicação contínua nos periódicos - Edivaldo Góis Junior; Alcides José Scaglia; João Paulo Borin; José Irineu Gorla; Valéria Bonganha (Universidade Estadual de Campinas, 2018)
Editorial.